2014
DOI: 10.1179/1362171814y.0000000246
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of martensite–austenite constituents in coarse grained heat affected zone of HSLA steel with varying Al contents

Abstract: The fine microstructure of martensite-austenite (M-A) constituents in simulated coarse grained heat affected zone (HAZ) of high strength low alloy steel with varying aluminium content (0?038 and 0?070 wt-%) at 100 kJ cm 21 heat input welding was investigated. The result shows that M-A constituents with 0?038%Al consisted of lath martensite and retained austenite. The retained austenite was distributed along the martensite lath. Whereas, the M-A constituents with 0?070%Al consisted of lath martensite and retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Therefore, more studies were concentrated on studying microstructures and properties of the heat-affected zone (HAZ) by varying peak temperatures, heat inputs, and alloy compositions. [7][8][9][10][11][12][13][14][15][16][17][18][19] In Reference 12 coarse austenite grain size associated with coarse M-A constituent along grain boundary was revealed as the dominant factor in promoting brittle fracture. The combination of fine prior austenite grain size and smaller M-A constituent was favorable in obtaining high toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more studies were concentrated on studying microstructures and properties of the heat-affected zone (HAZ) by varying peak temperatures, heat inputs, and alloy compositions. [7][8][9][10][11][12][13][14][15][16][17][18][19] In Reference 12 coarse austenite grain size associated with coarse M-A constituent along grain boundary was revealed as the dominant factor in promoting brittle fracture. The combination of fine prior austenite grain size and smaller M-A constituent was favorable in obtaining high toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of M-A constituents in the CGHAZ was reduced as a consequence of PAG size reduction (Refs. 23,24) by the cold wire addition. Quantitative analysis of the M-A regions indicates the fraction of M-A constituents in the CGHAZ with sizes larger than 2 m for the TSAW and cold-wire TSAW samples is 3.2 ± 0.2% and 1.0 ± 0.1%, respectively.…”
Section: Welding Researchmentioning
confidence: 99%
“…The M-A fraction in the CGHAZ of the TSAW and CWTSAW samples, calculated from the SEM micrographs (Fig. 7n, m), was 7.6 and 5.4 %, respectively, indicating a reduction in the fraction of M-A as a consequence of PAG size reduction [32][33][34][35] by cold-wire addition. The M-A fraction in the CGHAZ calculated from the optical micrographs (Fig.…”
Section: Cwtsaw and Tsaw Comparisonmentioning
confidence: 99%
“…Therefore, a coarser PAG size increases the fraction and size of the M-A constituent. Li et al [33] and Yu et al [35] showed that a coarse PAG size associated with a coarse M-A constituent is the dominant factor in promoting brittle fracture in the CGHAZ. Accordingly, there is a concurrent effect of both grain size refinement and M-A transformation, which plays a significant role in the strength, hardness, and toughness of the HAZ.…”
Section: Cwtsaw and Tsaw Comparisonmentioning
confidence: 99%